2019
DOI: 10.3389/fpls.2019.01437
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Y2H Screening Reveals Extensive Effector-Complex Formation

Abstract: During infection pathogens secrete small molecules, termed effectors, to manipulate and control the interaction with their specific hosts. Both the pathogen and the plant are under high selective pressure to rapidly adapt and co-evolve in what is usually referred to as molecular arms race. Components of the host’s immune system form a network that processes information about molecules with a foreign origin and damage-associated signals, integrating them with developmental and abiotic cues to adapt the plant’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Besides a second unidentified host target, another explanation for the virulence function of Nkd1 could be its interaction with one or more additional effectors which depend on Nkd1 to perform their function in maize. Systematic Y2H screens between U. maydis effectors indicate a massive effector interactome (Alcantara et al, 2019) and effector-effector interactions have been shown to impact virulence in other pathosystems (Tzfira et al, 2004, Magori and Citovsky, 2011, Cain et al, 2008. Even though we could not detect an interaction between Nkd1 and Jsi1 (Alcantara et al, 2019), Nkd1 could potentially interact with other U. maydis effectors during maize infection.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Besides a second unidentified host target, another explanation for the virulence function of Nkd1 could be its interaction with one or more additional effectors which depend on Nkd1 to perform their function in maize. Systematic Y2H screens between U. maydis effectors indicate a massive effector interactome (Alcantara et al, 2019) and effector-effector interactions have been shown to impact virulence in other pathosystems (Tzfira et al, 2004, Magori and Citovsky, 2011, Cain et al, 2008. Even though we could not detect an interaction between Nkd1 and Jsi1 (Alcantara et al, 2019), Nkd1 could potentially interact with other U. maydis effectors during maize infection.…”
Section: Discussionmentioning
confidence: 65%
“…Systematic Y2H screens between U. maydis effectors indicate a massive effector interactome (Alcantara et al, 2019) and effector-effector interactions have been shown to impact virulence in other pathosystems (Tzfira et al, 2004, Magori and Citovsky, 2011, Cain et al, 2008. Even though we could not detect an interaction between Nkd1 and Jsi1 (Alcantara et al, 2019), Nkd1 could potentially interact with other U. maydis effectors during maize infection. Therefore, analysis of Nkd1 interaction partners (plant or fungal) by IP-MS from infected maize tissue could help identify its second, non-redundant function.…”
Section: Discussionmentioning
confidence: 65%
“…The complex is formed during biotrophic growth and may be involved in effector translocation into plant cells [ 65 ]. A systematic yeast two-hybrid interaction screen of U. maydis effectors revealed extensive complex formation capacity, both by homo- as well as heterodimerization [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that each of the three genes individually affects virulence and that their role in virulence is independent of the presence of the other two genes. Of the five U. maydis tin1 genes, two were positive in the yeast two-hybrid effector interaction screen, and for one of them, tin1-2 , three putative interaction partners were retrieved [ 66 ]. Since these are identified as unrelated proteins, there is also no indication of complex formation between different Tin1 proteins in U. maydis .…”
Section: Discussionmentioning
confidence: 99%
“…Another two LysM receptor molecules OsCERK1 with CEBiP were able to form a hetero-oligomer complex to induce downstream immune responses ( Shimizu et al, 2010 ). Plant pathogenic effectors form complexes to overcome plant immunity to promote disease by interacting with themselves or with other effector proteins ( Alcântara et al, 2019 ). PsCRN63 in P. sojae was capable of suppressing PCD associated with PTI via self-dimerization ( Li et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%